Correlation Between Optic Nerve Head Parameters, RNFL, and CCT in Patients with Bilateral Pseudoexfoliation Using HRT-III. (January 2015) - Vergados, Athanasios; Papaconstantinou, Dimitrios; Diagourtas, Andreas; Theodossiadis, Panagiotis G.; Vergados, Ioannis; Georgalas, Ilias
Abstract Background: It is well-established that eyes with pseudoexfoliation syndrome (PXS) have higher intraocular pressure (IOP). Early diagnosis of preperimetric glaucoma will assist with better management of these patients. The aim of this study is to evaluate the optic nerve head (ONH) parameters and retinal nerve fiber layer (RNFL) thickness in subjects with bilateral PXS, bilateral pseudoexfoliative glaucoma (PXG) and normal, correlating these results with central corneal thickness (CCT). Design: This is a cross-sectional, case control study. All participants were from the Department of Ophthalmology, Athens University Medical School. Participants: A total of 55 eyes from 55 patients with PXS (27 eyes from 27 patients with PXG and 28 eyes from 28 normal subjects) were studied. Methods: Topographic measurements of the ONH and peripapillary RNFL thickness were performed using a confocal scanning laser ophthalmoscope (the Heidelberg Retina Tomograph-III). The outcomes were correlated with the CCT of the subjects. Main Outcome Measures: PXS subjects and age-matched normal subjects did not differ significantly in ONH parameters. RNFL thickness was significantly lower in the PXS group compared with the normal group, but there was not a statistically significant difference with the PXG patients. Regarding the correlation with CCT, the PXG group showed negative correlation with mean (p = 0.027) and max cup depth (p = 0.031), while PXS subjects revealed a positive correlation with RNFL thickness (p = 0.032). Conclusions: Our study showed that PXS subjects may be at greater risk of RNFL thinning, presenting a statistically significant positive association of the latter parameter with the CCT.